Care Work and Class : Domestic Workers' Struggle for Equal Rights in Latin America - Blofield, Merike (Book collections on Project MUSE., 2012)
"Examines the movement for labor reform among domestic workers in Latin America. Explores how domestic workers' mobilization, strategic alliances, and political windows of opportunity can lead to improved rights"--Provided by publisher.